IMAGING ANALYSIS OF PERIODONTAL STATUS IN A GROUP OF PATIENTS WITH OSTEOPOROSIS - Stoica George; Roxana Popescu; Andreea Diana Ilinca; Daniela Pomohaci; Balcos Carina; Alexandru Nemtoi; Sirghe Ana; Haba Danisia (Romanian Journal of Oral Rehabilitation)
Osteoporosis, a systemic disorder characterized by reduced bone density and microarchitectural deterioration, significantly affects bone health, including the mandibular and periodontal structures. This study aimed to evaluate the relationship between osteoporosis and periodontal pathology using imaging techniques in patients diagnosed with osteoporosis. Material and methods: The retrospective, descriptive study included 63 patients diagnosed with osteoporosis and other systemic conditions. Periodontal status was assessed clinically and paraclinically using the EGOHID evaluation system, while bone density was evaluated radiographically using indices such as the Mandibular Cortical Index (MCI), Mental Index (MI), Panoramic Mandibular Index (PMI), and Mandibular Cortical Width (MCW). Results: Results revealed significant periodontal involvement, with 42.9% of patients exhibiting moderate chronic marginal periodontitis and 46% severe periodontitis, more pronounced in the maxillary arch than the mandibular. Radiographic evaluation demonstrated that 58.7% of patients with osteoporosis had a slightly eroded mandibular cortex (C2), while 34.9% showed severe erosion (C3). The average cortical thickness (MCW) was significantly reduced in osteoporotic patients compared to non-osteoporotic individuals, highlighting its potential as a screening indicator. Conclusions: Osteoporosis is strongly associated with significant periodontal alterations and mandibular cortical resorption. These findings underline the importance of integrating bone health assessments into periodontal evaluations, emphasizing the role of imaging as a non-invasive screening tool for osteoporosis.